Undersökning av SCA Skogs gallrade skogar med hjälp av laserskanning - Ekskär, Hampus (2015)
The purpose of this study was to investigate the conditions of SCA Skog AB's thinned forests. A number of sites located in Västerbotten and Ångermanland were examined by using laser scanning to see the status of the forests after thinning. The study also investigates how well field surveys and laser scan figures are consistent. The report shows that high thinning grade will result in growth loss. Thinned stands of high thinning grade are more vulnerable to windthrow, this together with fertilised forests can be the cause of major damage.